Properties of Lightweight Concrete Containing Crumb Rubber as Partial Replacement of Fine Aggregates - Sanghar Bhutto, Abdul Rahman Mohd. Sam, Sajjad Ali Mangi, Ruhal Pervez Memon, Dhanesh Kumar (International Journal of Advanced Science and Technology, 2020)
Lightweight cement (LWC) can expand the volume of the blend while giving advantageous characteristics, for example, lessening the dead weight. It is lighter than the customary cement with an evaporate thickness to 1840 kg/m3. This paper presents results and talks about the utilization of morsel elastic to make lightweight cement and its impact on new and solidified properties of the LWC. Right off the bat, the portrayal of the piece elastic was completed including the strainer examination, thickness, water retention and explicit gravity. After that the ideal substitution measure of piece elastic as fine totals was resolved, trailed by the examination on the new and solidified properties of the planned LWC at 3, 7 and 28 days of restoring and contrasted and the NWC. The outcomes uncovered that the scrap elastic is a high-water retaining, low explicit gravity and low-thickness material. The 30% ideal measure of the scrap elastic as a fine total substitution was gotten to create the LWC, with droop estimation of 50 mm. The quality properties of LWC including compressive, flexural, changed compressive quality, ultrasonic heartbeat speed and bounce back number were seen as not exactly those of the NWC. Likewise, the LWC utilizing scrap elastic showed progressively flexible method of disappointment which demonstrates that the LWC utilizing morsel elastic can support the effect stacks and has generally high strength than NWC.